2016
DOI: 10.1186/s12880-016-0110-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three 18F-labeled carboxylic acids with 18F-FDG of the differentiation tumor from inflammation in model mice

Abstract: Background: The aim of this study was to compare the properties and feasibility of the glucose analog, 2-18

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…Albeit we showed a substantial tumor uptake in vivo with tumor-to-muscle ratio of up to four times for 1-TG (at 4h after injection), the uptake was less pronounced for 1-TG and 5-TG compared with 18 F-FDG for which previous studies using similar cell lines revealed tumor-to-muscle-ratios of 6:1 to 13:1 (15,16). This is in line with our in vitro work and could be a result of lower a nity of 1-TG and 5-TG to GLUT channels as compared to 18 F-FDG.…”
Section: Discussioncontrasting
confidence: 56%
“…Albeit we showed a substantial tumor uptake in vivo with tumor-to-muscle ratio of up to four times for 1-TG (at 4h after injection), the uptake was less pronounced for 1-TG and 5-TG compared with 18 F-FDG for which previous studies using similar cell lines revealed tumor-to-muscle-ratios of 6:1 to 13:1 (15,16). This is in line with our in vitro work and could be a result of lower a nity of 1-TG and 5-TG to GLUT channels as compared to 18 F-FDG.…”
Section: Discussioncontrasting
confidence: 56%
“…It has been reported that 2-[ 18 F]­FPA accumulated in prostate cancers with high tumor to background ratios, and it may be useful in the clinical diagnosis of prostate cancer in humans. In general, 18 F labeled fluoro-alkyl fatty acids displayed tumor uptakes. The mechanism(s) of uptake and their relationship with hypoxia conditions has not been reported, although 2-[ 18 F]­FPA did not showed preference for in vitro tumor cell uptake under hypoxia condition (Figure D).…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, most of these changes in F-AgÅPs + panipenem co-treatment group were much more obvious than that of mice treated with F-AgÅPs or panipenem alone ( Figure 6 F-H and Figure S2 A-D ). 18F-fluorodeoxyglucose (18F-FDG) is a radiotracer that is used to measure the glycolytic activity and a higher level of 18F-FDG uptake is demonstrated in inflammatory lesions 24 , 25 . Whole body imaging with 18F-FDG-PET/CT further confirmed that the combination of F-AgÅPs and panipenem caused a greater inhibition of inflammation in the E. coli -infected mice, as indicated by the trend of lower level of 18F-FDG uptake in F-AgÅPs + panipenem group compared to F-AgÅPs or panipenem group ( Figure 6 , I and J ).…”
Section: Resultsmentioning
confidence: 99%